2014
DOI: 10.3390/su6106622
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Urban Planning on Environmental Sustainability: A Focus Group Study in Finland

Abstract: Sustainable communities are promoted as a desirable policy goal and, in particular, local authorities are encouraged to contribute to climate change mitigation through urban planning. Furthermore, recent research takes a broad perspective on the environmental sustainability of urban areas and considers the environmental impact of all consumption. A focus group study was conducted in Finland for the purpose of examining how increased environmental awareness influences urban land use. The 32 participants of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 59 publications
0
37
0
1
Order By: Relevance
“…Environmental sustainability has become a focal point in urban development [9,10]. Urbanization seriously affects the natural environment, not only in terms of environmental pollution, but also in the deterioration of the geological environment, which can induce geohazards.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental sustainability has become a focal point in urban development [9,10]. Urbanization seriously affects the natural environment, not only in terms of environmental pollution, but also in the deterioration of the geological environment, which can induce geohazards.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of urban planning in fulfilling the environmental sustainability is related to the land use planning process, because it helps improving the environment. Furthermore, Säynäjoki, et al [12] found that environmental assessment leads the decision making in urban planning and that through considering the environment as part of the city political strategy agenda not as a contradiction of the municipalities decision making process. Also making a comprehensive study/evaluation regarding environmental impact assessment will help in determining the threshold capacity of environment.…”
Section: The Role Of Planning and The Required Proceduresmentioning
confidence: 99%
“…It is worth mentioning that the European Community Commission Guide (1992) indicated the importance of using the environmental issues and the environmental capacity tools to form the base that will support the development plans. "Considering the limited potential and power of ecological context of cities, urban sustainable development would be possible if it is based on the local and environmental characteristics in the same format and observing the fundamental principles of sustainable development" [12].…”
Section: The Role Of Planning and The Required Proceduresmentioning
confidence: 99%
“…. However, planning alone is not sufficient to achieve sustainability targets (Stenstadvold 1996;Säynäjoki et al 2014). There are several other factors and actors influencing the urban development.…”
Section: Trondheim's Pathway Towards Urban Densificationmentioning
confidence: 99%